(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2023)
This scientific paper presents a comprehensive investigation into fluid flows in channels employing the Finite Element Method (FEM). Understanding and analyzing flow behavior in channels is essential for numerous engineering applications, such as optimizing fluid transport systems, designing efficient heat exchangers, and mitigating environmental concerns related to water resources. The FEM, a numerical technique widely used for solving partial differential equations, provides a robust platform for simulating and examining complex fluid dynamics in various channel geometries.